Tissue-Specific and Geographical Variation in Endophytic Fungi of Ageratina adenophora and Fungal Associations With the Environment - Fang, Kai; Miao, Yi-Fang; Chen, Lin; Zhou, Jie; Yang, Zhi-Ping; Dong, Xing-Fan; Zhang, Han-Bo (Frontiers in Microbiology, 2019)
To understand the distribution of the cultivable fungal community in plant tissues and the associations of these fungi with their surrounding environments during the geographical expansion of an invasive plant, Ageratina adenophora, we isolated the cultivable fungi from 72 plant tissues, 12 soils and 12 air samples collected from 6 areas in Yunnan Province, China. A total of 4066 isolates were investigated, including 1641 endophytic fungi, 233 withered leaf fungi, 1255 fungi from air and 937 fungi from soil. These fungi were divided into 458 and 201 OTUs with unique and 97% ITS gene sequence identity, respectively. Phylogenetic analysis showed that the fungi belonged to 4 phyla, including Ascomycota (94.20%), Basidiomycota (2.71%), Mortierellomycota (3.03%) and Mucoromycota (0.07%). The dominant genera of cultivable endophytic fungi were Colletotrichum (34.61%), Diaporthe (17.24%), Allophoma (8.03%), and Fusarium (4.44%). Colletotrichum and Diaporthe were primarily isolated from mature leaves, Allophoma from stems, and Fusarium from roots, indicating that the enrichment of endophytic fungi is tissue-specific and fungi rarely grew systemically within A. adenophora. In the surrounding environment, Alternaria (21.46%), Allophoma (19.31%), Xylaria (18.45%) and Didymella (18.03%) were dominant in the withered leaves, Cladosporium (22.86%), Trichoderma (14.27%) and Epicoccum (9.83%) were dominant in the canopy air, and Trichoderma (27.27%) and Mortierella (20.46%) were dominant in the rhizosphere soils. Further analysis revealed that the cultivable endophytic fungi changed across geographic areas and showed a certain degree of variation in different tissues of A. adenophora. The cultivable fungi in mature and withered leaves fluctuated more than those in roots and stems. We also found that some cultivable endophytic fungi might undergo tissue-to-tissue migration and that the stem could be a transport tissue by which airborne fungi infect roots. Finally, we provided evidence that the fungal community within A. adenophora was partially shared with the contiguous environment. The data suggested a frequent interaction between fungi associated with A. adenophora and those in surrounding environments, reflecting a compromise driven by both functional requirements for plant growth and local environmental conditions.